Cancer interventions with faith-based organizations: a scoping review - Yeary, Karen Hye-cheon Kim; Allen, Jennifer D.; Arredondo, Elva; Atemnkeng, Jamia; Buzcu-Guven, Birnur; Day, Kelsey R.; Dicarlo, Elizabeth; Formagini, Taynara; Kwon, Simona C.; McElfish, Pearl; McNeill, Lorna H.; Newton, Robert L.; et al. (Cancer causes & control, 2025)
Purpose Faith-based organizations (FBOs) have been recognized as a critical partner to reach underserved, marginalized populations in the U.S. for disease prevention and health promotion. FBOs have been successfully engaged to lower risk for leading causes of death, including cancer, but despite the proliferation of FBO cancer intervention research, a comprehensive review is lacking. Methods We conducted a PRISMA Scoping Review to ascertain the impact of FBO cancer interventions. Seven bibliographical databases were used to search for articles evaluating cancer interventions reporting quantitative outcomes in which places of worship in the U.S. served as the research location. Study characteristics and results data were extracted by two independent extractors. Results Thirty-six studies were included. All FBOs were Christian churches with healthy populations. Breast (25%), prostate (22%), and colorectal (17%) were the primary cancers targeted and cancer screening was the primary outcome of 75% of studies. Sixty-nine percent (k = 25) reported significant results in cancer-related outcomes from baseline to post-intervention follow-up, with 100% of studies in Korean American communities (k = 7) reporting significant results. Conclusion FBO interventions can successfully increase preventative screening across numerous cancer types in diverse communities, particularly in Korean Americans. Additional FBO cancer interventions that aim to reduce inequities in other cancers (e.g., lung) that disproportionately affect Korean Americans and have not been targeted are warranted. Expanding current investigations of FBO collaborations with other faiths (besides Christian) to include cancer prevention and control would further realize FBOs’ untapped potential.